2001
DOI: 10.1016/s0896-6273(01)00353-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Transcription to the Neuromuscular Synapse

Abstract: Concomitant with innervation, genes coding for components of the neuromuscular junction become exclusively expressed in subsynaptic nuclei. A six-base pair element, the N box, can confer synapse-specific transcription to the acetylcholine nicotinic receptor delta and epsilon subunit, utrophin, and acetylcholine esterase genes. N box-dependent synaptic expression is stimulated by the nerve-derived signal agrin and the trophic factor neuregulin, which triggers the MAPK and JNK signaling pathways, to ultimately a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
166
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(172 citation statements)
references
References 47 publications
5
166
0
1
Order By: Relevance
“…It had long been thought that motor axons approach a muscle that is regionally unspecialized and induce postsynaptic differentiation by releasing signals that focally initiate transcriptional and post-translational responses in the muscle Pettigrew, 1974, 1976;Burden, 1998;Kandel et al, 2000;Sanes and Lichtman, 2001;Schaeffer et al, 2001). These studies implicated motor neuron-derived Agrin, a glycosylated proteoglycan, as the critical neural signal for inducing postsynaptic differentiation and the muscle-specific receptor tyrosine kinase, MuSK, a component of the Agrin receptor, as the transducer for clustering AChRs and activating AChR gene expression at synaptic sites (Burden, 1998;Glass et al, 1996a;Glass et al, 1996b;Glass and Yancopoulos, 1997;Sanes and Lichtman, 2001;Schaeffer et al, 2001;Valenzuela et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It had long been thought that motor axons approach a muscle that is regionally unspecialized and induce postsynaptic differentiation by releasing signals that focally initiate transcriptional and post-translational responses in the muscle Pettigrew, 1974, 1976;Burden, 1998;Kandel et al, 2000;Sanes and Lichtman, 2001;Schaeffer et al, 2001). These studies implicated motor neuron-derived Agrin, a glycosylated proteoglycan, as the critical neural signal for inducing postsynaptic differentiation and the muscle-specific receptor tyrosine kinase, MuSK, a component of the Agrin receptor, as the transducer for clustering AChRs and activating AChR gene expression at synaptic sites (Burden, 1998;Glass et al, 1996a;Glass et al, 1996b;Glass and Yancopoulos, 1997;Sanes and Lichtman, 2001;Schaeffer et al, 2001;Valenzuela et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…These studies implicated motor neuron-derived Agrin, a glycosylated proteoglycan, as the critical neural signal for inducing postsynaptic differentiation and the muscle-specific receptor tyrosine kinase, MuSK, a component of the Agrin receptor, as the transducer for clustering AChRs and activating AChR gene expression at synaptic sites (Burden, 1998;Glass et al, 1996a;Glass et al, 1996b;Glass and Yancopoulos, 1997;Sanes and Lichtman, 2001;Schaeffer et al, 2001;Valenzuela et al, 1995). This neuro-centric view of neuromuscular synapse formation, however, has been challenged by recent experiments, which showed that mammalian muscle is spatially patterned independent of innervation.…”
Section: Introductionmentioning
confidence: 99%
“…Such a wealth of transcriptional behaviors have to be encoded in the promoters that control the expression of the subunit genes (see Duclert and Changeux (1995) and Schaeffer et al (2001) for model system of the motor endplate and Bessis et al (1995) for the neuronal nAChRs). However, a given stretch of DNA can only encrypt a limited amount of transcriptional information.…”
Section: Promoters and Regulation Of Expressionmentioning
confidence: 99%
“…Indeed, these genes share some features of transcriptional control. For example, the nACHR subunit and utrophin-A promoter N-box play a critical role in regulating expression levels and more importantly in restricting expression to the NMJ (Schaeffer et al, 2001). We and others (Gramolini et al, 1999a;Khurana et al, 1999) have shown that the nerve-derived growth factor heregulin (HRG) causes a N-box-mediated increase in utrophin-A promoter activity via extracellular signal-regulated kinase-dependent activation of the Ets-related transcription factor complex GABP␣/␤, in a manner similar to that noted in the nACHR␦ and nACHR subunit promoters (Falls et al, 1993;Koike et al, 1995;Sapru et al, 1998; This article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E06 -12-1069) on May 16, 2007. 1998).…”
Section: Introductionmentioning
confidence: 99%